Is low volume HIIT enough to induce changes in oxygen uptake kinetics? - Curto, D.; Pinto, R.; Espada, M.; Infante, J.; Alves, F. B.; Reis, J. F. (Journal of Human Sport & Exercise, 2019)
The literature shows that endurance training induces a speeding of the initial oxygen uptake kinetics (VO2k) and maximal oxygen consumption (VO2max). However, the specific characteristics of training that optimizes said parameters is not yet clearly established. We aimed to investigate the effects of low volume high intensity interval training (HIIT) on VO2max and VO2k during intensity transitions within the moderate domain. Twenty healthy active subjects were randomly assigned to either complete 12 sessions of low volume HIIT over a 4-wk period (HIIT group) or a control group (CON) that did not change their regular physical activity. Before (PRE) and after (POST) the intervention period, subjects completed on the treadmill an incremental test and square wave transitions to moderate intensity exercise. In all tests, pulmonary VO2 was collected breath-by-breath (Metamax3b, Cortex, Germany). The parameters of the VO2k for the moderate exercise were determined using a monoexponential model. All the physiological variables did not change from PRE to POST in the CON group. However, HIIT training improved the VO2max and maximal aerobic velocity (MAV), whereas there were no significant changes in the VO2k. Four weeks of low volume HIIT was not sufficient to induce changes on VO2k in moderate running. Nevertheless, this training provoked improvements in VO2peak and MAV, consequently low volume HIIT seems to be a time-efficient approach to increase these parameters. The dissociation between changes in VO2k and VO2max seems to reflect the different underlying mechanisms regulating these adaptations.